Digital Image Processing using Python Programme for Laplace Transforms: An Introduction - Jawahar, G. Gomathi; Rathi, R. Selva; Singh, Jagmohan; Shalu, Shon Mathew (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Improving the quality and visual appearance of digital images, filter design, system analysis and make them more suitable for a wide range of applications using Python Programme for laplace transforms.